Cisternostomy for Management of Intracranial Hypertension in Severe Traumatic Brain Injury; Case Report and Literature Review - Masoudi, Mohammad Sadegh (Bull Emerg Trauma, 2016)
Main goal in the management of patients with severe traumatic brain injury (TBI) is control of intracranial pressure (ICP). Decompressive craniectomy is an accepted technique for control of refractory intracranial hypertension in patients with severe TBI. Because of high complication rate after decompressive craniectomy, new techniques such as basal cisternostomy have developed. We herein report a case of severe TBI in a 13-year-old boy treated by cisternostomy. The patient was admitted following a motor vehicle accident. Brain CT scan showed diffuse brain edema, left frontal contusion and posterior interhemispheric subdural hematoma. The patient underwent ICP monitoring. Subsequently, with 26 mmHg mean-value of ICP, he was treated surgically by cisternostomy technique. A progressive improvement of the neurological conditions in the following hours. After 5 days the boy was discharged and in the 3-months follow-up he was completely recovered. Cisternostomy could be an appropriate alternative to decompressive craniectomy for management of intracranial hypertension in patietns with sever TBI.